Interaction of Rayleigh waves with periodic baffles - Danicki, E. (Archives of Acoustics, 2002)
Rayleigh waves in two solids separated by an air gap containing two alternate periodic in-plane baffle systems are considered. A Bragg reflection of the waves occurs when the distance between the baffle planes and between baffles and solids are half wavelength long in air. This may support an idea of contactless application of comb transducers to generate Rayleigh waves. The analysis is carried out using the BIS expansion method to account for the wavefield singularity at the baffle edges.